The Implementation of English Language Teaching Management from An English-mediated Early Childhood Education School in Salatiga - Mozes Kurniawan (Universitas Kristen Satya Wacana, 2020)
English is a language that has been widely studied at the educational level. The introduction of English at kindergarten level is also growing these days. In practice, the use of English in kindergarten needs to be optimized, especially with good governance of English learning. This study aims to capture best practice ideas from an accredited private kindergarten school in the city of Salatiga. Respondents of this study were the principal, teacher representatives and parents in the research object. Data collection techniques in this study used semi-structured interviews. Acquisition data were analyzed qualitatively by reducing and categorizing according to management aspects. Research results showed that at the planning stage, the school properly manages the vision and mission, curriculum, and school policies that support learning with English as the language of instruction. At the organizing stage, the school regulates the recruitment of human resources for educators and external parties who collaborate in learning at the school so that language communication qualifications are maintained. For the implementation stage, various interesting learning methods were developed and added to the exposure of English content so that children were used to it and continued to develop their language skills. Then, at the supervision stage, schools assess the learning process and teacher qualifications including providing assistance to maintain the quality they already have.